Distance Pedagogical Education in the Conditions of the Coronavirus - Tretyakova, Tatyana V. (2020)
The relevance of the study is due to the problem of finding optimal solutions for organizing training sessions, the need to form the personality of a teacher in a difficult social and pedagogical situation. The leading research method is a pedagogical experiment on the organization of distance learning for students, the method of theoretical substantiation of the formation of the "Digital Educational Ecosystem" project, the method of practical implementation of the digital environment in work with educational organizations and schoolchildren. This article presents practical solutions for organizing training sessions, pedagogical practices, conducting state final certification through the use of interactive educational platforms, social networks, and instant messengers. An equally significant result of the study is the educational component of the formation of a future teacher in a difficult social situation.